Please manipulate these equations as specified, so that I can compare them to the other problems I need to do.

1. (w/v) = (g/(v-w)) to get 1/v + 1/w = 1/g

2. (w - g) = f²(1/(v-g)) into 1/v + 1/w = 1/g

Printable View

- February 10th 2010, 01:44 AMAudaciityEquation Manipulation
Please manipulate these equations as specified, so that I can compare them to the other problems I need to do.

1. (w/v) = (g/(v-w)) to get 1/v + 1/w = 1/g

2. (w - g) = f²(1/(v-g)) into 1/v + 1/w = 1/g - February 10th 2010, 01:59 AMGrandadMore information please
- February 10th 2010, 02:13 AMAudaciity
They are equations, not functions.

I am asking people to show the steps to rearrange (and manipulate) the equations.

How do I get from w/v = g/(v-w)

to 1/v + 1/w = 1/g ?

How do I get from w-g = f²(1/(v-g))

to 1/v + 1/w = 1/g ? - February 10th 2010, 02:37 AMGrandad
- February 10th 2010, 02:52 AMHallsofIvy
The point Grandad was making is that you

**can't**change from one to the other, they simply aren't equivalent. From w/v= g/(v-w), you can get that 1/g= v/(w(v-w)) but that is NOT equal to 1/v+ 1/w.

The second one has an "f" in it but the equation you want to change it into doesn't. Again, that is NOT possible.